Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.3389/fnsys.2015.00021
|View full text |Cite
|
Sign up to set email alerts
|

Stronger efferent suppression of cochlear neural potentials by contralateral acoustic stimulation in awake than in anesthetized chinchilla

Abstract: There are two types of sensory cells in the mammalian cochlea, inner hair cells, which make synaptic contact with auditory-nerve afferent fibers, and outer hair cells that are innervated by crossed and uncrossed medial olivocochlear (MOC) efferent fibers. Contralateral acoustic stimulation activates the uncrossed efferent MOC fibers reducing cochlear neural responses, thus modifying the input to the central auditory system. The chinchilla, among all studied mammals, displays the lowest percentage of uncrossed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
1
19
0
1
Order By: Relevance
“…Given the periodic nature of our probe stimuli, it is also possible that our FFRs included contributions from cochlear microphonics, especially at higher frequencies. Our few observations of FFR enhancement with CAS at higher probe frequencies are consistent with reports that the cochlear microphonic amplitude grows with MOC reflex activation (e.g., Fex, 1959; Aedo et al, 2015). In pilot work for this experiment, we observed that forward masking obliterated F1-FFR, F2-FFR, and CDP-FFR components in four participants, suggesting a neural origin.…”
Section: Discussionsupporting
confidence: 92%
“…Given the periodic nature of our probe stimuli, it is also possible that our FFRs included contributions from cochlear microphonics, especially at higher frequencies. Our few observations of FFR enhancement with CAS at higher probe frequencies are consistent with reports that the cochlear microphonic amplitude grows with MOC reflex activation (e.g., Fex, 1959; Aedo et al, 2015). In pilot work for this experiment, we observed that forward masking obliterated F1-FFR, F2-FFR, and CDP-FFR components in four participants, suggesting a neural origin.…”
Section: Discussionsupporting
confidence: 92%
“…It is unlikely that this resilience is mediated by the middle-ear muscle reflex (MEMR) or medial olivocochlear reflex (MOCR), based on the observations that central anesthetics attenuate the strength of both reflexes ( MEMR : Borg et al, 1975; Valero et al, 2017; MOCR : Chambers et al, 2013; Aedo et al, 2015). Such resistance might arise from the mechanical strength of the reticular lamina and the tight junctions that also provide the diffusion barrier between endolymph and perilymphatic scalae.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Longenecker and Lobarinas have both found PPI thresholds (assessed in quiet) were similar to ABR wave 1 amplitude losses when animals were noise-exposed; yet found PPI thresholds remained stable, whereas ABR thresholds recovered (Longenecker and Galazyuk, 2016 ; Longenecker et al, 2016 ; Lobarinas et al, 2017 ). Moreover, as PPI testing does not involve anesthesia, efferent feedback is maximized (Maison et al, 2012 ; Aedo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%